Correlation of PM2.5 pollution and daily mortality rate of cardiovascular and cerebrovascular diseases in Northeast China through PM2.5 sources analysis - Hong Qianqi; Zhao Yang; Wang Jing; Sun Hongyan; Deng Lanxin; Cao Jingjing; Wang Cheng (Frigid Zone Medicine)
This study aims to evaluate the relationship between PM2.5 concentration and daily mortality rate from cardiovascular and cerebrovascular diseases (CCVD) in cold regions of northern China, as well as to identify the primary sources of PM2.5.